DOES POLITICS STILL MATTER? NEOLIBERALIZATION PROCESSES, PARTY GOVERNMENT AND NEW PATTERNS OF URBAN POLITICS IN BRAZILIAN LOCAL GOVERNMENTS - Nelson, Carvalho Rojas de (Teoria & Pesquisa Revista de Ciência Política, 2022)
As the neoliberalization process has unfolded in Latin America in the last two decades, cities and city-regions have become a privileged target of volatile capital flows in search of investment opportunities. Cities, in their turn, severely affected by a huge national fiscal deficit, have put in place new regulatory practices – such as Public Private Partnerships (PPPs) and Urban Consortium Operations (UCOs) – as a means to promote local growth. As this process has unfolded, one question should be tackled: have growth policies been pursued to the detriment of redistributive policies - in line with Peterson’s (1981) hypothesis-, no matter voters’ and elected mayors’ ideological positions? We tested Peterson’s hypothesis to 5570 Brazilian municipalities firstly correlating local growth policies with executive officer’s ideology and party affiliation. Then, through multivariate and longitudinal analysis we correlated growth policies, on the hand, and redistributive policies, on the other, with both local political data and sociodemographic data, such as city size and human development index (HDI). The preliminary findings of the study showed that growth strategies that rely on new regulatory tools such as PPPs and UCOs have been carried out both in left- and right-leaning municipalities and states; whereas ideology does not seem to impact growth strategies, sociodemographic factors, such as city size and HDI, do affect growth policy directions. Next, we analyzed the variation in welfare policies outcomes among Brazilian municipalities. Again, the ideological factor plays a minor impact on this variation